The effect of PARP and PLK1 dual inhibition on the expression of important protein signaling pathways, DNA damage, and molecular docking scores against MCF-7 and MDA-MB-231 breast cancer cell lines - Gok, Ozlem; Aslan, Abdullah; Erdogan, Mehmet Kadir; Uslu, Harun; Toy, Yusuf; Agca, Can Ali; Gundogdu, Ramazan (Springer London Ltd, 2026)
BackgroundSmall molecule PARP inhibitors, such as olaparib, have been developed as part of personalized cancer treatment strategies.AimThis study investigated the synthetic lethality between the PARP enzyme in breast cancer cell lines.MethodsThe anti-cancer effects of combining the PARP inhibitor olaparib with the small molecule PLK1 inhibitor BI-2536 on MCF-7 and MDA-MB-231 breast cancer cells were assessed through in vitro cell viability (MTT) and clonogenic cytotoxicity analyses. The impact of olaparib and BI-2536 treatment on cell cycle and DNA damage response proteins was analyzed using Western blotting. BRCA2 expression was silenced using RNA interference technology, and the manipulation of BRCA2 gene expression in MCF-7 breast cancer cells was confirmed by Western blotting. Cell viability and colony survival were evaluated in BRCA2-effective and BRCA2-defective MCF-7 cells. Additionally, molecular docking analyses provided insights into the functioning of protein signaling pathways.ResultsOur results indicate that the combined treatment with olaparib and BI-2536 significantly reduces the viability of MCF-7 and MDA-MB-231 breast cancer cells and inhibits their colony formation ability. This combination therapy demonstrated a synergistic cytotoxic effect, causing potentiated DNA damage induction in these breast cancer cells compared to individual treatments.ConclusionsThe increased expression of PLK1, p53, p21, gamma H2AX, Nrf-2, cyclin E, A, and B1, along with the decreased expression of HER-2, NF-kappa B, and cyclin D1 in breast cancer cells, suggests that PLK1 inhibition can enhance the efficacy of PARP inhibitors.
Keywords: BI-2536; DNA damage; MCF-7; MDA-MB-231; Olaparib